Perioperative Nursing Roles in Stroke Prevention and Management - Tippakon, Pattamon; Ratanatherawichian, Yananan; Vichitvejpaisal, Phongthara (Journal of The Royal Thai Army Nurses, 2025)
This review explores the multifaceted aspects of perioperative stroke management, focusing on the critical role of perioperative nurses in stroke prevention and intervention. Beginning with an overview of stroke types, incidence, and risk factors in the perioperative period, the review delves into the identification of stroke symptoms in the PACU, emphasizing the importance of early detection and assessment. Furthermore, it delves into existing stroke protocols, interventions, and management strategies, emphasizing the pivotal role of interdisciplinary collaboration in enhancing patient outcomes. Underscoring the necessity for ongoing education, awareness, and proactive involvement in stroke care initiatives within perioperative nursing practice. Additionally, emerging trends and technologies in perioperative stroke management are examined, alongside challenges and opportunities for enhancing the care of surgical patients. This comprehensive review provides insights, recommendations, and a call to action for advancing perioperative stroke care.